Recent development in magnesium oxychloride cement. (12th July 2018) - Guo, Yingying; Zhang, Yixia; Soe, Khin; Pulham, Mark
Abstract : This paper presents a review for the key literatures on magnesium oxychloride cement (MOC) to establish a comprehensive and insightful understanding of MOC. The main aim of this review is to identify the most common problems in the development and application of the MOC and the various methods to solve these problems. The characteristics of MOC including composition of hydration phases, strength development, and durability are reviewed. In particular, the various factors influencing the water resistance of MOC, the most critical characteristics of MOC, such as the reactivity of magnesium oxide, additives, and curing conditions are reviewed. Finally, the methods to improve water resistance and its related issues of MOC from the literature are summarized and future research is proposed.